Historical geomorphology analysis of the stream of the Euphrates River, its branches Al-Atshan & Al-Subul, from Shannafia to Samawah for the period (1799 - 1969), and the impact of the Naggarat on the geomorphology of its rivers - Ahmad S. Yasien Al-Gurairy ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The article focused on studying the historical - geomorphology changes of the stream of the Euphrates River and its branches in the territory between Al-Shinnafiya and Samawa - central Iraq. Where used old maps from 1799 to 1944 AD, aerial photographs from the 1960s, topographic maps, and modern satellite images. From the data analysis, it became clear that there are two river streams that no one had ever heard of before, linking the two main branches of the Euphrates in the region (Al-Atshan and Al-Subul), which were founded when the Euphrates stream shifted from its fourth phase to its fifth phase (from the stream of Shatt Al-Hillah to the stream of Shatt Al-Hindia). However, these two linking streams, penetrating the bedrock of Umm al-Akf Island, did not take long for their water to be cut off from both of their intakes at the two branches of the Euphrates, and then they dried up and subsided to become a relic after the mid-forties of the last century. The researcher believes that the end of the two connecting streams is due to several reasons, the most prominent of which is the occurrence of the recent tectonic activation process in the region, which resulted in the rejuvenation of the Euphrates River stream, represented by the phenomenon of Naggarat. The second reason is due to the accumulation of sediments from flood mud in their channels, when Umm al-Akaf turned into a large marsh after each flood, and caused the flow of water to stop in them, as they were lying under the waters of the Marsh (Hor) of Allah, after each flood. The study also indicated that the stream of Shatt Al-Atshan turned into a small stream during the fourth phase of the Euphrates (Shatt al-Hillah) and that it was not part of the main Euphrates stream in its fourth phase, and got waters from a group of streams south of Heet to the north of Diwaniyah. The study also confirmed the existence of another phase of the Euphrates streams (sixth phase - middle and end of the Pleistocene) that has not been given enough research and study, as this phase extends to the Euphrates stream from south Hit - west of Karbala - west of Najaf, and the stream of Shatt Al-Atshan south to west of Basra, then to its downstream is in the Iraqi Khor Abdullah Al-Tamimi, in the Gulf of Basra (The Arabian Gulf).